Beyond recidivism: reconceptualizing success through relational health for trauma-exposed youth experiencing juvenile justice involvement - Zelechoski, Amanda D.; Bohner, Janet; Perry, Bruce D. (Frontiers in Psychology, 2024)
Youth who have histories of trauma exposure face unique barriers and needs in navigating the juvenile justice system. Accordingly, reliance on recidivism as the primary "success" metric falls short for trauma-impacted youth and may actually prolong justice involvement. Caregivers and juvenile justice professionals (i.e., judges, attorneys, detention and probation staff, case managers, and mental health clinicians) often struggle to identify and adequately address these challenges and pitfalls. This policy brief provides an overview of specialized considerations for traumatized youth with respect to common policies and practices, namely mandated placement, treatment, and timelines. Specific examples and actionable recommendations are provided to assist decisionmakers and treatment providers with systemic efforts to more appropriately and effectively customize juvenile justice policies and programs for these extremely vulnerable youth.